Fundamentos filosóficos y sociológicos de la inclusión educativa y la atención a la diversidad - Fernández Rodríguez, Martha María (2016)
The philosophical and sociological foundations of educational inclusion and attention to diversity were presented. The aim of this work was to provide educational practice to those involved in educational inclusion and attention to diversity, in this departing from the theoretical underpinnings which allow get a better preparation in this process. This article was part of a training for inclusion and attention to diversity given to the teachers at Colegio Femenino Espíritu Santo in Guayaquil. Theoretical methods such as analysis and synthesis, from the abstract to the concrete and induction and deduction were used. The achieved result for the trainees was a greater preparation in thephilosophical and sociological fundamentals leading the process of inclusion and attention to diversity.